Injuries to Iliac Arteries Following Blunt Trauma of the Abdomen - SUDA, Hisao; NATSUAKI, Masafumi; NAITO, Kouzo; UENO, Tetsuya; NAKAYAMA, Yoshihiro; MINATO, Naoki; ITOH, Tsuyoshi (Japanese Journal of Cardiovascular Surgery, 1993)
We present three cases of injured iliac arteries due to blunt abdominal trauma in traffic accidents. We performed emergency operations on these patients. Two of them received interposition of artificial prosthesis, and one received extraanatomical bypass. Fasciotomy was needed for compartment syndrome in 2 cases and one of them suffered a fractured pelvis with rupture of the ipsilateral femoral vein. One case was complicated with laceration of the mesentery. The postoperative course was almost uneventful in 2 cases but one died 8 days after operation because of subsequent multiple organ failure due to renal failure with necrosis of the small intestine of unknown cause. The diagnostic difficulties in such injuries depend on the existence of complications and different obstructive mechanisms from the penetrating injuries. Adequate and prompt diagnosis based on the clinically suspicious signs including weakness and discrepancy of the pulse are required.